2012
DOI: 10.2139/ssrn.2178691
|View full text |Cite
|
Sign up to set email alerts
|

Shirts Today, Skins Tomorrow: Dual Contests and the Effects of Fragmentation in Self-Determination Disputes

Abstract: While theoretical models of conflict often treat actors as unitary, most selfdetermination groups are fragmented into a number of competing internal factions. This article presents a framework for understanding the ''dual contests'' that selfdetermination groups engage in-the first with their host state and the second between co-ethnic factions within groups. Using a new data set of the number of factions within a sample of self-determination groups from 1960 to 2008, the authors find that competition between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(113 citation statements)
references
References 61 publications
2
111
0
Order By: Relevance
“…Figure 2B also shows a greater risk of recurrence by old rebel actors in civil conflicts with multiple actors, regardless of whether the multiple actors are other rebel factions (multiple dyads) or progovernment militias. This is to be expected as armed groups that operate in an environment that is highly competitive for members have perpetual incentives to improve institutional cohesion to avoid defection to other groups (Cunningham, Bakke and Seymour 2012;Nygård and Weintraub 2015).…”
Section: Victorymentioning
confidence: 99%
“…Figure 2B also shows a greater risk of recurrence by old rebel actors in civil conflicts with multiple actors, regardless of whether the multiple actors are other rebel factions (multiple dyads) or progovernment militias. This is to be expected as armed groups that operate in an environment that is highly competitive for members have perpetual incentives to improve institutional cohesion to avoid defection to other groups (Cunningham, Bakke and Seymour 2012;Nygård and Weintraub 2015).…”
Section: Victorymentioning
confidence: 99%
“…A second line of argument states that conflicts with multiple groups are longer in duration (Cunningham, 2006), more violent (Bloom, 2004;Cunningham, Bakke and Seymour, 2012), and are harder to settle (Oye, 1985). The literature points to a number of important reasons why a greater number of factions might make post-conflict stability difficult.…”
Section: Number Of Factionsmentioning
confidence: 99%
“…Cunningham (2006), for example, empirically shows that unless the number of factions is quite small, post-conflict stability will remain unlikely. Similarly, Cunningham, Bakke and Seymour (2012) suggested that all other things being equal, it would be easier to organise and maintain durable peace in divided societies of smaller number of factions than one with multiple factions. Likewise, Oye (1985) also concluded that durable peace is difficult to organise in a divided society with multiple factions.…”
Section: Number Of Factionsmentioning
confidence: 99%
“…A number of case studies have empirically explored possible causes for splintering. Several studies have found that competition among rebels, particularly when competing for the "affection" of a particular ethnic group, may encourage outbidding in extremism and in the level of violence (Bloom 2005, Pearlman 2008/2009, Cunningham 2011, Cunningham, Bakke and Seymour. 2012, and Lilja 2012.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When rebels cooperate, the number of political acts produced is controlled and restricted, thus leaving space for productive activity (Tullock, 1974and Collier and Hoeffler, 1998. However, if rebels splinter, competitive pressure increases the number of political acts produced at the expense of productive acts (Bloom 2005, Cunningham 2011, Cunningham et. al.…”
Section: Introductionmentioning
confidence: 99%